2012
DOI: 10.1016/j.neuron.2012.08.037
|View full text |Cite
|
Sign up to set email alerts
|

The Fibroblast Growth Factor Family: Neuromodulation of Affective Behavior

Abstract: In this review we propose a broader view of the role of the fibroblast growth factor (FGF) family in modulating brain function. We suggest that some of the FGF ligands together with the FGF receptors are altered in individuals with affective disorder and modulate emotionality in animal models. Thus, we propose that members of the FGF family may be genetic predisposing factors for anxiety, depression or substance abuse; that they play a key organizing role during early development but continue to play a central… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
130
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 140 publications
(135 citation statements)
references
References 152 publications
5
130
0
Order By: Relevance
“…An emerging literature that began with studies in human depressed brains and was followed up by a range of studies in animals models strongly implicates FGF2 in the modulation of affect, especially in decreasing anxiety behavior (25,27). Our own work has shown that neonatal FGF2 resulted in a long-term decrease in anxiety-like behavior in bLR which naturally exhibit high anxiety behavior (28).…”
Section: Role Of Fgf2 In Altering the Levels Of Repressive H3k9me3 Anmentioning
confidence: 96%
See 3 more Smart Citations
“…An emerging literature that began with studies in human depressed brains and was followed up by a range of studies in animals models strongly implicates FGF2 in the modulation of affect, especially in decreasing anxiety behavior (25,27). Our own work has shown that neonatal FGF2 resulted in a long-term decrease in anxiety-like behavior in bLR which naturally exhibit high anxiety behavior (28).…”
Section: Role Of Fgf2 In Altering the Levels Of Repressive H3k9me3 Anmentioning
confidence: 96%
“…Because FGF2 plays a key role as an endogenous anxiolytic and shows higher expression levels in the less anxious bHRs (25,28), we used a ChIP assay to investigate the association levels of various modified histone at the FGF2 gene. Compared with bLRs, negligible association was observed for the repressive H3K9me3 (P < 0.001) at the FGF2 gene promoter in bHR rat HC, amygdala, and NAcc ( Fig.…”
Section: Endogenous Levels Of Methylated Repressive Histone Protein Hmentioning
confidence: 99%
See 2 more Smart Citations
“…fibroblast growth factor 9 | major depression | anxiety | hippocampus | affect T he neurotrophic hypothesis of major depressive disorder (MDD) posits that the neurobiological basis for mood disorders may be due to the dysregulation of growth factors and their effects on brain circuitry (1,2). This hypothesis is supported by gene expression profiling experiments in postmortem human brains that implicate the fibroblast growth factor (FGF) family and other neurotrophins in MDD (3,4).…”
mentioning
confidence: 99%